Show me the money : managing cost savings - Ellram, Lisa M., (SAGE Business Cases., 2020)
When a successful buyer of direct materials (those materials that go directly into a product) changes roles to manage indirect spend (goods and services that are not directly incorporated into the product being manufactured), she discovers critical differences in amount spent, categories, suppliers, and cost savings. A major difference is a new set of stakeholders—the budget owners for each spend category. Much of the savings she can help generate in the direct indirect spend category won't "count" toward her cost-savings goals and achieving performance metrics, because they are considered cost avoidance, which is not valued in their management accounting system. This case is beneficial to students in purchasing/supply chain classes as well as managerial accounting classes that deal with measurement and management control systems.